Sāk vitt ok vītt of verǫld hverja - Koutsomichalis, Marinos (My University, 2020)
A film by Marinos Koutsomichalis. Pivoting on the homonymous media art/research project. Filmed in various locations across Iceland, Norway, and the Faroe Islands in 2018 and 2019.